Homogenization kinetics of a nickel-based superalloy produced by powder bed fusion laser sintering. (1st April 2017) - Zhang, Fan; Levine, Lyle E.; Allen, Andrew J.; Campbell, Carelyn E.; Lass, Eric A.; Cheruvathur, Sudha; Stoudt, Mark R.; Williams, Maureen E.; Idell, Yaakov
Abstract: Additively manufactured (AM) metal components often exhibit fine dendritic microstructures and elemental segregation due to the initial rapid solidification and subsequent melting and cooling during the build process, which without homogenization would adversely affect materials performance. In this letter, we report in situ observation of the homogenization kinetics of an AM nickel-based superalloy using synchrotron small angle X-ray scattering. The identified kinetic time scale is in good agreement with thermodynamic diffusion simulation predictions using microstructural dimensions acquired by ex situ scanning electron microscopy. These findings could serve as a recipe for predicting, observing, and validating homogenization treatments in AM materials. Graphical abstract: